(untitled) (Hilo Analítico, 2025)
Change is a constant process of becoming, due to the interaction of forces, some of which have already been fully identified, others less well known, and still others that remain unknown. At the socio-economic level, variables that predict the behavior of markets are constantly analyzed, and generally obliterate indicators of exclusion and marginality. At the individual level, differences are recognized, but become trends when interpretation is sought. History, generally seen through the eyes of the present, makes explicit some aspects of change, which appear linked to the event, a birth with blood and fire, from which the entrepreneurs of violence and war profit. In such cases, there is no democratic transition, based on conflict and negotiation through words: there is a violent struggle for power, resulting in the new (old) order.